Immunomodulatory effects of Bacillus firmus - Trebichavský, I; Mára, M; Sinkora, J; Splíchal, I; Stĕpánková, R (Folia microbiologica, 1997)
3-day-old miniature piglets were stimulated in vivo with Bacillus firmus by the intraperitoneal or intragastric route for 1 d. Cells containing IgA and IgG2 were detected in the ileum in all stimulated but not in control animals. The frequency of blood CD3+ cells increased after intraperitoneal administration of B. firmus, the ratio of polymorphonuclears to lymphocytes increased in all stimulated piglets. B. firmus induced antitumor immunity in rats with transplanted Yoshida sarcoma cells. Granular lymphocytes and dead tumor cells were found in peritoneal exudate of stimulated animals. B. firmus induced IFN-gamma synthesis in human blood lymphocytes stimulated in vitro for 1 d. The amount of TNF-alpha produced by these stimulated human peripheral blood mononuclears (PBMC) was lower than that of PBMC stimulated with some other bacterial immunomodulators. Cells containing TGF-beta or IL-8 were not found in human PBMC stimulated with B. firmus.
Keywords: prasata; Swine; Immunoglobulin G; gastrointestinální intubace; Rats, Wistar; Interferon-gamma; Tumor Necrosis Factor-alpha; leukocyty mononukleární; Bacterial Vaccines; imunoglobulin G; interferon gama; potkani Wistar; Swine, Miniature; Sarcoma, Yoshida; ileum; krysa rodu Rattus; Immunotherapy; kultivované buňky; Adjuvants, Immunologic; Animals; Intubation, Gastrointestinal; lidé; Leukocytes, Mononuclear; Bacillus; bakteriální vakcíny; injekce intraperitoneální; Injections, Intraperitoneal; Ileum; Humans; adjuvancia imunologická; zvířata; sarkom Yoshidův; Rats; imunoterapie; imunoglobulin A; TNF-alfa; Cells, Cultured; Immunoglobulin A; miniaturní prasata